Influence of Two-stage Tooth Profile Modification on Transmission Accuracy of Robot Precision Reducer - Xuetao Qiao; Ke Jia; Cunfu Yan; Ze Yang; Peng Wang; Fang Li (Jixie chuandong)
Based on the involutes and cycloid gear profile equation，3D parametric models of involute gear and cycloid gear are respectively established in Creo with considering modification，and the whole machine parametric model of RV-20E precision reducer is obtained. The model of the whole machine is introduced into Adams to establish a virtual prototype，and the kinematics simulation is carried out to obtain the angular velocity curves of involutes planetary gear，cycloid wheel and planetary frame. The correctness of the virtual prototype is verified by theoretical calculation results. The influence of two-stage modification on the transmission accuracy of the robot precision reducer is studied. Six virtual prototypes are respectively established when considering the first stage modification combined with modification variables. According to the simulation results，the running smoothness of the left and right involutes planetary gears with tooth profile modification is improved by 86.5% and 82.6% respectively. Compared with the cycloid gear modification only considered，the two-stage modification combined with cycloid gear modification is considered，the motion transmission of the precision reducer is more stable，the transmission accuracy is increased by 1.8%，and the operation smoothness is increased by 30.5%.